Building pathways out of poverty in Baidoa: A randomized controlled trial: Evidence from the midline survey - Leight, Jessica; Hirvonen, Kalle; Karachiwalla, Naureen; Rakshit, Deboleena (International Food Policy Research Institute, 2024)
Somalia is one of the poorest countries in the world, and severe poverty, ongoing armed conflict, and recurring droughts and floodings have created a humanitarian crisis characterized by a high level of internal displacement. Baidoa city – the site of this evaluation – hosts 517 internally displaced persons (IDP) sites with almost 600,000 households, and 64 percent of the individuals living in these sites are women and girls. According to the 2nd Somali High Frequency Survey (Pape and Karamba 2019), poverty is particularly high in IDP settlements (along with rural areas), exacerbated by high unemployment rates and an absence of income-generating opportunities.